A Simulation Model for Narrow Band Gap Ferroelectric Materials. Issue 9 (12th July 2020) - Ducharne, Benjamin; Juuti, Jari; Bai, Yang
Abstract: Various ferroelectric simulation models have been developed in recent decades in order to study the mechanisms and predict the behaviors of ferroelectrics by simulating their hysteresis loops. Conventional ferroelectrics have wide optical band gaps (>2.7 eV), making them difficult to respond to visible light. Although their ferroelectricity can be affected by higher‐energy radiation like ultraviolet, little attention is paid to the development of their models incorporating light‐dependent factors. However, in recent years, narrow band gap (<2.5 eV) ferroelectrics have been discovered and are increasingly researched. These special ferroelectrics effectively absorb visible light and hence exhibit strongly light‐dependent ferroelectricity, triggering potentially a broad range of applications. Therefore, there is a need to develop a model for these ferroelectrics in order to predict their behavior under visible light. Such a model is also needed to improve the understanding of the interaction mechanisms between light and domains. In this paper, a ferroelectric simulation model based on the Jiles–Atherton theory considering light dependence is developed for the first time, and its accuracy is validated by experiments. The model shows an average error of 7.5% on polarization values compared to experimental results and thus can be employed to reliably predict photo‐induced ferroelectricity. Abstract : Photoferroelectrics are stepping from purely theoretical studies into application‐oriented research thanks to recently developed narrow band gap ferroelectrics. Among all physical models, ferroelectric simulations are lacking, especially for visible light interactive factors. This hinders application research, which requires the prediction of light‐induced ferroelectricity. This paper fills in this blank area by providing a reliable ferroelectric simulation model incorporating incident lighting conditions.